Some Characteristics of Similarities - Siddikovich, Yaqub Saidov; Murodova, Gulchiroy Muhiddinovna (International Journal on Human-Computing Studies, 2023)
The article discusses the analysis of artistic similarities that are important in the text of a work of art. The scientific views of several scientists on the similarities are discussed. Types of similarities, peculiarities of Isaac's Ibrat gazelles and poems are analyzed and explained by various considerations.